Enhanced performance of bistable energy harvesters using auxiliary magnet oscillators - Nguyen, Minh Sang (2018)
Recently, an emerging energy harvesting technology has been considered as a potential alternative to chemical batteries for self-powered electronic devices. Energy harvesting is a process to capture ambient energy sources, convert them to electrical energy, and provide power for small wireless micro-devices. Such an energy harvesting technology is an important part of ‘deploy-and-forget’ wireless sensor networks, which must be essential for Internet-of-Things paradigms in Industry 4.0. Among various types of energy harvesters, a vibration energy harvester (VEH) is of great interest to researchers owing to the ubiquity of vibration energy sources, high energy density, and the ease of application. Recent research on a VEH system has been aimed particularly at broadening its operating frequency band, thereby enabling it to operate properly under an actual environment of ambient vibration sources with time-varying and/or multiple frequency components. Especially, during the past decade, a bistable energy harvester (BEH) has been one of the most promising designs of broadband VEH systems. A potential well escape phenomenon that occurs in a bistable system is well known to lead to a large-amplitude oscillation of a BEH (thus, produce high output power) in a broad frequency band. However, this mechanism has its intrinsic limitation that a potential energy barrier possibly prevents the broadband operation of a BEH under relatively weak excitation. As a research effort to overcome this drawback, new types of BEH systems with auxiliary magnet oscillators are proposed in this thesis and their nonlinear dynamic behaviors and the associated performance are theoretically and experimentally investigated and discussed. This thesis is composed of two research subjects concerning bistable energy harvesters with i) horizontal and ii) vertical auxiliary magnet oscillators, which Abstract ii are called BEH-HO and BEH-VO, respectively. Each of these BEHs is composed of a piezoelectric bimorph cantilever beam and two permanent magnets. One magnet is attached to the free end of the piezoelectric beam, and the other is an external magnet acting as an auxiliary magnet oscillator.For the BEH-HO, an external magnet is designed to be movable in the horizontal direction. A mechanical rectifier is additionally inserted, such that the excessive oscillation of the external magnet is prohibited. The rectified half-sine motion of the auxiliary magnet oscillator tends to reduce the saddle barrier in the restoring potential energy function of the BEH-HO, leading to an easier occurrence of potential well escape phenomenon. Consequently, the operating frequency band of the BEH-HO is broadened in comparison to the conventional BEH under the same excitation condition. For BEH-VO, an external magnet is attached to the free end of another cantilever beam in order to allow its vertical motion. In this case, it is found that the complicated nonlinear behaviors of the BEH-VO can be described with a novel concept of phase-dependent potential energy. In particular, there are two distinct dynamic regimes which depend on the relative motion of two magnets; i) the outof-phase regime observed at the first primary resonance and ii) the in-phase regime at the second primary resonance. Moreover, the secondary resonances of the BEH-VO as well as the primary resonances can also be important routes to high-energy orbit motions. These multiple nonlinear resonances are properly arranged in series on the frequency domain, such that their frequency bands are gradually connected with the increase of excitation intensity and merged into a very broad single operating frequency band. Such a bridging effect notably enhances the broadband performance of the BEH-VO, when compared with its conventional counterpart. AbstractiiiThe mathematical models for the abovementioned BEH-HO and BEH-VO systems are first derived based on the Euler-Bernoulli beam theory, linear piezoelectricity, and magnetic charge model. A series of nonlinear analyses are performed to investigate the nonlinear characteristics of the BEH-HO and BEHVO systems in terms of energy harvesting performance. All the theoretical results are confirmed by comparing them with experimental ones. The results show a promising potential for the practical application of the proposed BEH-HO and BEH-VO systems for broadband vibration energy harvesting.